1998
DOI: 10.1093/ndt/13.4.975
|View full text |Cite
|
Sign up to set email alerts
|

Safety of ultrasound-guided percutaneous renal biopsy-retrospective analysis of 1090 consecutive cases

Abstract: If contraindications, especially high blood pressure and abnormal haemostasis, are respected, ultrasound-guided percutaneous renal biopsy with an automated biopsy device is safe. Skilled operators obtain satisfactory amounts of kidney tissue in almost all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
154
2
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 0 publications
15
154
2
5
Order By: Relevance
“…This is comparable to previous work, where major hemorrhagic complication rates after native renal biopsies were reported as ranging from 1 to 8% (15,(17)(18)(19)(20)(21). This study included 148 patients with a known monoclonal gammopathy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is comparable to previous work, where major hemorrhagic complication rates after native renal biopsies were reported as ranging from 1 to 8% (15,(17)(18)(19)(20)(21). This study included 148 patients with a known monoclonal gammopathy.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies have investigated the potential risk factors for complications after percutaneous renal biopsy (17)(18)(19)(20). Although monoclonal gammopathy-associated disease has been suggested to confer an increased risk of hemorrhagic complications (8,9), the current evidence supporting this theory is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a systematic review and metaanalysis of 34 retrospective and prospective studies including 9474 adult patients who underwent biopsy of the native kidney, using ultrasound realtime imaging and automatic biopsy device, the overall incidence of bleeding complications were: Transient gross haematuria 3.5%, request for transfusion therapy 0.9%, demand on angiographic control of bleeding 0.6%, request for nephrectomy for control of bleeding 0.01% and death 0.02% [26] . Thus, the risk of using invasive procedures to stop bleeding is very rare [27,28] . More frequently we can treat this complication with medical treatment such as administration of endovenous fluid and/or blood products [29] .…”
Section: Complicationsmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that diagnosis and therapy are modified in about 40% of cases following renal biopsy [36] and that the technique used alters the clinical prognosis in about 50% of cases [40]. Therefore, renal biopsy is considered to be the diagnostic procedure of choice for many patients in whom renal disease is suspected [14].…”
mentioning
confidence: 99%